Living life to the fullest with Ehlers-Danlos syndrome : a guide for a person living with EDS to achieve a better quality of life - Muldowney, Kevin (Denver, Colorado : Outskirts Press, 2015)
"This book was written to teach people with Ehlers-Danlos Syndrome (EDS) how to systematically progress through an exercise program to allow their muscles to support many joint subluxations commonly associated with this genetic disorder. This will allow people living wih EDS to have less pain throughout their body."--Back cover.
Keywords: Ehlers-Danlos syndrome; Exercise therapy